Superconducting properties of the noncentrosymmetric superconductor TaOs. (26th October 2017) - Singh, D; Sajilesh, K P; Marik, S; Hillier, A D; Singh, R P
Abstract: The noncentrosymmetric superconductor TaOs has been characterized using x-ray diffraction, resistivity, magnetization, and specific heat measurements. Magnetization and specific heat measurements show a bulk superconducting transition at 2.07 K. These measurements suggest that TaOs is a weakly coupled type-II superconductor. The electronic specific heat in the superconducting state can be explained by the single-gap BCS model, suggesting s-wave superconductivity in TaOs.